Solve the following terms \[{(81)^{ - 1}} \times {3^{ - 5}} \times {3^9} \times {(64)^{\dfrac{5}{6}}} \times {(\sqrt[3]{3})^6}\]
Answer
Verified
484.8k+ views
Hint: Indices: The base \[x\] raised to the power of \[p\] is equal to the multiplication of\[x\] p times.
\[{x^p} = x \times x \times x \times x \ldots \ldots .p{\rm{ }}times\], where x is the base and p is the indices.
Formula used:
Power rule:
\({({x^m})^n} = {x^{mn}}\)
\[{x^{{m^n}}} = {x^{({m^n})}}\]
To derive the solution of the given problem, we first need to solve each and every part of it. For that we have to use the indices formula and make the base as smallest as possible .Then multiply all the parts to find the value of the given problem.
Complete step by step answer:
We have to find out, \[{(81)^{ - 1}} \times {3^{ - 5}} \times {3^9} \times {(64)^{\dfrac{5}{6}}} \times {(\sqrt[3]{3})^6}\]
We will solve the problem part by part,
Let us consider the first part
The first part in the given problem is $(81)$\[^{ - 1}\]
Let us solve it, we get,
\[\Rightarrow {(81)^{ - 1}} = \dfrac{1}{{81}}\]
Let us write the denominator in terms of powers we get,
\[\Rightarrow \dfrac{1}{{81}} = \dfrac{1}{{{3^4}}}\]
\[\Rightarrow \dfrac{1}{{{3^4}}} = {({3^4})^{ - 1}}\]
Let us use the power rule in the above term,
\[\Rightarrow {({3^4})^{ - 1}} = {3^{ - 4}}\]
We have got\[{(81)^{ - 1}} = {3^{ - 4}}\].
Let us consider the second term,
The second term is \[{(64)^{\dfrac{5}{6}}}\]
Let us express the number in terms of power we get,
\[\Rightarrow {(64)^{\dfrac{5}{6}}} = {({2^6})^{\dfrac{5}{6}}}\]
By using the power rule in the above equation we get,
\[\Rightarrow {({2^6})^{\dfrac{5}{6}}} = {2^{6 \times \dfrac{5}{6}}}\]
On solving the above equation we get,
\[\Rightarrow {2^{6 \times \dfrac{5}{6}}} = {2^5}\]
We have got,\[{(64)^{\dfrac{5}{6}}} = {2^5}\]
Now let us consider another term\[{(\sqrt[3]{3})^6}\]
Let us express the root in terms of power we get,
\[\Rightarrow {(\sqrt[3]{3})^6} = {({3^{\dfrac{1}{3}}})^6}\]
Using the power rule in the above expression we get,
\[\Rightarrow {({3^{\dfrac{1}{3}}})^6} = {3^{\dfrac{1}{3} \times 6}}\]
And on further solving we get,
\[ {3^{\dfrac{1}{3} \times 6}} = {3^2}\]
Hence we have got,\[{(\sqrt[3]{3})^6} = {3^2}\]
Here we have expressed every term as a power of some base.
Therefore, by multiplying all the parts we have,
\[\Rightarrow {(81)^{ - 1}} \times {3^{ - 5}} \times {3^9} \times {(64)^{\dfrac{5}{6}}} \times {(\sqrt[3]{3})^6}\]\[ = {3^{ - 4}} \times {3^{ - 5}} \times {3^9} \times {2^5} \times {3^2}\]
We know that if the bases are same we can add the power using that identity we have,
\[{3^{ - 4}} \times {3^{ - 5}} \times {3^9} \times {2^5} \times {3^2}\]\[ = {3^{ - 4 + ( - 5) + 9 + 2}} \times {2^5}\]
And on further solving we get,
\[ {3^2} \times 32\]
\[= 9 \times 32\]
\[\Rightarrow {(81)^{ - 1}} \times {3^{ - 5}} \times {3^9} \times {(64)^{\dfrac{5}{6}}} \times {(\sqrt[3]{3})^6}\]\[ = 288\]
$\therefore$ We have found that \[{(81)^{ - 1}} \times {3^{-5}} \times {3^9} \times {(64)^{\dfrac{5}{6}}} \times {(\sqrt[3]{3})^6} = 288\].
Note:
We have used the following power values in the calculation\[\;81 = 3\;64 = 2\;\sqrt[3]{3} = {3^{\dfrac{1}{3}}}\] .
Also by expressing every as a power of some smaller term we have arrived at the result easily.
\[{x^p} = x \times x \times x \times x \ldots \ldots .p{\rm{ }}times\], where x is the base and p is the indices.
Formula used:
Power rule:
\({({x^m})^n} = {x^{mn}}\)
\[{x^{{m^n}}} = {x^{({m^n})}}\]
To derive the solution of the given problem, we first need to solve each and every part of it. For that we have to use the indices formula and make the base as smallest as possible .Then multiply all the parts to find the value of the given problem.
Complete step by step answer:
We have to find out, \[{(81)^{ - 1}} \times {3^{ - 5}} \times {3^9} \times {(64)^{\dfrac{5}{6}}} \times {(\sqrt[3]{3})^6}\]
We will solve the problem part by part,
Let us consider the first part
The first part in the given problem is $(81)$\[^{ - 1}\]
Let us solve it, we get,
\[\Rightarrow {(81)^{ - 1}} = \dfrac{1}{{81}}\]
Let us write the denominator in terms of powers we get,
\[\Rightarrow \dfrac{1}{{81}} = \dfrac{1}{{{3^4}}}\]
\[\Rightarrow \dfrac{1}{{{3^4}}} = {({3^4})^{ - 1}}\]
Let us use the power rule in the above term,
\[\Rightarrow {({3^4})^{ - 1}} = {3^{ - 4}}\]
We have got\[{(81)^{ - 1}} = {3^{ - 4}}\].
Let us consider the second term,
The second term is \[{(64)^{\dfrac{5}{6}}}\]
Let us express the number in terms of power we get,
\[\Rightarrow {(64)^{\dfrac{5}{6}}} = {({2^6})^{\dfrac{5}{6}}}\]
By using the power rule in the above equation we get,
\[\Rightarrow {({2^6})^{\dfrac{5}{6}}} = {2^{6 \times \dfrac{5}{6}}}\]
On solving the above equation we get,
\[\Rightarrow {2^{6 \times \dfrac{5}{6}}} = {2^5}\]
We have got,\[{(64)^{\dfrac{5}{6}}} = {2^5}\]
Now let us consider another term\[{(\sqrt[3]{3})^6}\]
Let us express the root in terms of power we get,
\[\Rightarrow {(\sqrt[3]{3})^6} = {({3^{\dfrac{1}{3}}})^6}\]
Using the power rule in the above expression we get,
\[\Rightarrow {({3^{\dfrac{1}{3}}})^6} = {3^{\dfrac{1}{3} \times 6}}\]
And on further solving we get,
\[ {3^{\dfrac{1}{3} \times 6}} = {3^2}\]
Hence we have got,\[{(\sqrt[3]{3})^6} = {3^2}\]
Here we have expressed every term as a power of some base.
Therefore, by multiplying all the parts we have,
\[\Rightarrow {(81)^{ - 1}} \times {3^{ - 5}} \times {3^9} \times {(64)^{\dfrac{5}{6}}} \times {(\sqrt[3]{3})^6}\]\[ = {3^{ - 4}} \times {3^{ - 5}} \times {3^9} \times {2^5} \times {3^2}\]
We know that if the bases are same we can add the power using that identity we have,
\[{3^{ - 4}} \times {3^{ - 5}} \times {3^9} \times {2^5} \times {3^2}\]\[ = {3^{ - 4 + ( - 5) + 9 + 2}} \times {2^5}\]
And on further solving we get,
\[ {3^2} \times 32\]
\[= 9 \times 32\]
\[\Rightarrow {(81)^{ - 1}} \times {3^{ - 5}} \times {3^9} \times {(64)^{\dfrac{5}{6}}} \times {(\sqrt[3]{3})^6}\]\[ = 288\]
$\therefore$ We have found that \[{(81)^{ - 1}} \times {3^{-5}} \times {3^9} \times {(64)^{\dfrac{5}{6}}} \times {(\sqrt[3]{3})^6} = 288\].
Note:
We have used the following power values in the calculation\[\;81 = 3\;64 = 2\;\sqrt[3]{3} = {3^{\dfrac{1}{3}}}\] .
Also by expressing every as a power of some smaller term we have arrived at the result easily.
Recently Updated Pages
Master Class 11 Accountancy: Engaging Questions & Answers for Success
Express the following as a fraction and simplify a class 7 maths CBSE
The length and width of a rectangle are in ratio of class 7 maths CBSE
The ratio of the income to the expenditure of a family class 7 maths CBSE
How do you write 025 million in scientific notatio class 7 maths CBSE
How do you convert 295 meters per second to kilometers class 7 maths CBSE
Trending doubts
When people say No pun intended what does that mea class 8 english CBSE
In Indian rupees 1 trillion is equal to how many c class 8 maths CBSE
How many ounces are in 500 mL class 8 maths CBSE
Which king started the organization of the Kumbh fair class 8 social science CBSE
What is BLO What is the full form of BLO class 8 social science CBSE
Advantages and disadvantages of science